2004
DOI: 10.1038/sj.cdd.4401393
|View full text |Cite
|
Sign up to set email alerts
|

ZBP-89-induced apoptosis is p53-independent and requires JNK

Abstract: ZBP-89 induces apoptosis in human gastrointestinal cancer cells through a p53-independent mechanism. To understand the apoptotic pathway regulated by ZBP-89, we identified downstream signal transduction targets. Ectopic expression of ZBP-89 induced apoptosis through the mitochondrial pathway and was accompanied by activation of all three MAP kinase subfamilies: JNK1/2, ERK1/2 and p38 MAP kinase. ZBP-89-induced apoptosis was markedly enhanced by ERK inhibition with U0126. In contrast, inhibiting JNK with a JNK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 68 publications
4
38
1
Order By: Relevance
“…Although Akt activation is known as a survival and anti-apoptotic response, in the present study, we found that silibinin enhances UVB-induced Akt activation, which appears to be a stress response consistent with recent reports showing that Akt is one of the substrates of DNA-PK, a genotoxic stress response gene (44). To further support this notion and to identify the pathway(s) regulating Akt activation in JB6 cells under our study conditions, we used LY294002, which in addition to its inhibitory activity toward PI 3-kinase, is also known as a potent and selective inhibitor of DNA-PK (39), which belongs to the PI 3-kinase-like kinase having a PI 3-kinase homology domain (10,39). Pre-treatment of cells with LY294002 completely abolished the silibinin-caused increase in Akt-Ser 473 phosphorylation as well as p53-Ser 15 phosphorylation and accumulation by UVB irradiation.…”
Section: Discussionmentioning
confidence: 96%
“…Although Akt activation is known as a survival and anti-apoptotic response, in the present study, we found that silibinin enhances UVB-induced Akt activation, which appears to be a stress response consistent with recent reports showing that Akt is one of the substrates of DNA-PK, a genotoxic stress response gene (44). To further support this notion and to identify the pathway(s) regulating Akt activation in JB6 cells under our study conditions, we used LY294002, which in addition to its inhibitory activity toward PI 3-kinase, is also known as a potent and selective inhibitor of DNA-PK (39), which belongs to the PI 3-kinase-like kinase having a PI 3-kinase homology domain (10,39). Pre-treatment of cells with LY294002 completely abolished the silibinin-caused increase in Akt-Ser 473 phosphorylation as well as p53-Ser 15 phosphorylation and accumulation by UVB irradiation.…”
Section: Discussionmentioning
confidence: 96%
“…The overexpression of the tumour suppressor LKB1 or the ZBP-89 protein generates an apoptotic cell death that is p53-independent but JNKdependent, suggesting that this kinase may be an apoptosis instigator (Bai et al, 2004;Lee et al, 2006). Furthermore, it has been demonstrated that sirtuins can induce apoptosis mediated by JNK signalling independent of Dp53 (Griswold et al, 2008).…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihmentioning
confidence: 99%
“…Direct binding of ZBP89 to p53, which causes growth arrest via p53 retention in the nucleus (Bai & Merchant 2001), has been described as well. Interestingly, ZBP89 induces apoptosis in a JNK-dependent, but p53-independent manner (Bai et al 2004). In summary, ZBP89 inhibits cell proliferation (Remington et al 1997), induces apoptosis, and cooperates or competes with SP1 promoter binding sites, for example, in the STAT1 (Bai & Merchant 2003) and the vimentin promoter (Zhang et al 2003).…”
Section: Discussionmentioning
confidence: 96%
“…We cloned two sequences into the pSuppressor Neo vector. One sequence is active in suppressing ZBP89 transcripts (5 0 -AAGATCGAAGTATGCCTCACCTT-3 0 ), and for control we used the same sequence mutated in five bps (5 0 -AAGATCGAACGTGTCCTCACCTT-3 0 ) which is ineffective in ZBP89 suppression (Bai et al 2004). The constructs were linearized and transfected into SHSY5Y cells.…”
Section: Generation Of Stable Zbp89 Knockdown Shsy5y Cellsmentioning
confidence: 99%